2013
DOI: 10.3390/rs5010224
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Land Observing Satellite Phased Array Type L-Band SAR (ALOS PALSAR) to Inform the Conservation of Mangroves: Sundarbans as a Case Study

Abstract: Abstract:Mangroves are an important bulkhead against climate change: they afford protection for coastal areas from tidal waves and cyclones, and are among the most carbon-rich forests in the tropics. As such, protection of mangroves is an urgent priority. This work provides some new information on patterns of degradation in the Sundarbans, the largest contiguous mangrove forest in the world, which are home to more than 35 reptile species, 120 commercial fish species, 300 bird species and 32 mammal species. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 36 publications
2
48
0
2
Order By: Relevance
“…Santoro et al [51] who studied ALOS PALSAR (Advanced Land Observing Satellite Phased Array type L-band Synthetic Aperture Radar) data found that better classification results were obtained from HV than from HH polarization. Dabrowska-Zielinska et al [43] and Conforth et al [52] also presented wetland classification using ALOS PALSAR data acquired in HV polarization. Flores De Santiago et al [53] found that a combination of HH and HV polarization modes from ALOS PALSAR data was better at separating forested wetlands using an object-based classification approach.…”
Section: Classification Of Wetland Vegetation Habitat Typesmentioning
confidence: 99%
“…Santoro et al [51] who studied ALOS PALSAR (Advanced Land Observing Satellite Phased Array type L-band Synthetic Aperture Radar) data found that better classification results were obtained from HV than from HH polarization. Dabrowska-Zielinska et al [43] and Conforth et al [52] also presented wetland classification using ALOS PALSAR data acquired in HV polarization. Flores De Santiago et al [53] found that a combination of HH and HV polarization modes from ALOS PALSAR data was better at separating forested wetlands using an object-based classification approach.…”
Section: Classification Of Wetland Vegetation Habitat Typesmentioning
confidence: 99%
“…According to Santoro et al [21], who studied ALOS PALSAR data, better classification results are obtained from HV-than from HH-polarization. Cornforth et al [22] illustrated the detection and mapping of mangroves based on ALOS PALSAR data. They found that HV polarization is more sensitive to vegetation structure and biomass than HH polarization.…”
Section: Classification Of Wetlands Vegetation Habitatsmentioning
confidence: 99%
“…SAR data have also shown potential in conservation planning. TerraSAR-X time series identified swath events in protected semi-natural grasslands within 11-day intervals (Schuster et al 2011), whereas changes in PALSAR backscatter data mapped coastline retreat and health degradation in a large mangrove forest (Cornforth et al 2013). …”
Section: Regulating Servicesmentioning
confidence: 99%